Impact of alcohol use on 30-day complication and readmission rates after elective spinal fusion (≥2 levels) for adult spine deformity: a single institutional study of 1,010 patients - Elsamadicy, Aladine A.; Adogwa, Owoicho; Vuong, Victoria D.; Sergesketter, Amanda; Reddy, Gireesh; Cheng, Joseph; Bagley, Carlos A.; Karikari, Isaac O. (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: Alcohol use has been shown to affect surgical outcomes. However, it is unknown what effect alcohol use has on postoperative complications or readmission rates in spinal fusion surgery. The aim of this study is to determine the impact of preoperative alcohol use on 30-day readmission rates or the complications profile after adult elective spinal fusion for deformity correction (≥2 levels). Methods: The medical records of 1,010 adult patients undergoing elective spinal fusion (≥2 levels) for spinal deformities at a major academic institution from 2005 to 2015 were reviewed. We identified 317 (31.4%) patients who had a history of alcohol prior to surgery and 693 (68.6%) patients who had no history of pre-operative alcohol consumption. The demographics, comorbidities, intra- and 30-day post-operative complication and readmission rates were collected for each patient. The primary outcome investigated in this study was the rate of 30-day readmissions and postoperative complication rates. Results: Baseline characteristics were similar between both cohorts. Intraoperative variables and the immediate postoperative complications profile were mostly similar between both cohorts. Overall, there was no significant difference between the 30-day readmission rates or complications profile between the two cohorts. Conclusions: Our study suggests there is no significant difference in 30-day readmission or complication rates among adult patients with or without preoperative alcohol use undergoing elective correction of spinal deformities.